2022
DOI: 10.1021/acs.chemrev.2c00468
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Synthesis of Metal Nanocrystals: From Asymmetrical Growth to Symmetry Breaking

Abstract: Nanocrystals offer a unique platform for tailoring the physicochemical properties of solid materials to enhance their performances in various applications. While most work on controlling their shapes revolves around symmetrical growth, the introduction of asymmetrical growth and thus symmetry breaking has also emerged as a powerful route to enrich metal nanocrystals with new shapes and complex morphologies as well as unprecedented properties and functionalities. The success of this route critically relies on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 500 publications
(1,327 reference statements)
2
50
0
Order By: Relevance
“…38 For Au@Pd core-porous shell NPs with conformal and epitaxial Pd shells, tensile strain in the Pd is expected due to the lattice mismatch (4.6%, where the cell parameters of Au and Pd are 4.08 and 3.89 Å, respectively) between Au and Pd. 39 As noted above, heterogeneous nucleation of Pd occurred at the surface of the Au seed; Pd islands nucleated at the Au surface may mediate the further growth of coarse, porous Pd shells in the presence of CTAC. Therefore, epitaxial growth of Pd shells on the surface of Au NPs did not occur.…”
Section: Xrd Analysismentioning
confidence: 85%
“…38 For Au@Pd core-porous shell NPs with conformal and epitaxial Pd shells, tensile strain in the Pd is expected due to the lattice mismatch (4.6%, where the cell parameters of Au and Pd are 4.08 and 3.89 Å, respectively) between Au and Pd. 39 As noted above, heterogeneous nucleation of Pd occurred at the surface of the Au seed; Pd islands nucleated at the Au surface may mediate the further growth of coarse, porous Pd shells in the presence of CTAC. Therefore, epitaxial growth of Pd shells on the surface of Au NPs did not occur.…”
Section: Xrd Analysismentioning
confidence: 85%
“…The loading amounts of different metals were adjusted by regulating the feeding amount of the metal salt precursor. However, Au and Pd NPs did not have such a feature because the strong Ostwald ripening effect facilitated the reduced metal particles to agglomerate during the metal salt precursor reduction process and exposed the HW surfaces [ 50 ], which might be related to the growth rate of the crystal faces of various metals and the surface energy. The Au-HW composite materials were shown in Figure 3 e. The Au nanoparticles were uniformly supported on the surface of HW, and the Au particle size was ~15 nm by the size statistics.…”
Section: Resultsmentioning
confidence: 99%
“…According to literature reports, this dimensional change of AuNR caused by an increase in the amount of silver ions is well in line with the structural evolution governed by the Ag-UPD effect. 50,53,54 According to the TEM images, AuNRs acquired from different amounts of silver ions all display good size uniformity, suggesting a good monodispersity of the particle. Based on the size measurement of AuNRs, it is shown that as the amount of silver ions was increased from 0.15 mL to 0.8 mL, the length of AuNRs increases from 41.8 AE 1.7 nm to 83.2 AE 3.3 nm, and the diameter decreases from 16.9 AE 0.7 nm to 10.5 AE 0.6 nm (see Table S1 and Fig.…”
Section: Effects Of Silver Ionsmentioning
confidence: 99%